The Structural and Functional Study of Efflux Pumps Belonging to the RND Transporters Family from Gram-Negative Bacteria - Broutin, Isabelle; Vargiu, Attilio V; Venter, Henrietta; Phan, Gilles (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Antimicrobial-resistant bacterial infections are a major and costly public health concern. Several pathogens are already pan-resistant, representing a major cause of mortality in patients suffering from nosocomial infections. Drug efflux pumps, which remove compounds from the bacterial cell, thereby lowering the antimicrobial concentration to sub-toxic levels, play a major role in multidrug resistance. In this Special Issue, we present up-to-date knowledge of the mechanism of RND efflux pumps, the identification and characterization of efflux pumps from emerging pathogens and their role in antimicrobial resistance, and progress made on the development of specific inhibitors. This collection of data could serve as a basis for antimicrobial drug discovery aimed at inhibiting drug efflux pumps to reverse resistance in some of the most resistant pathogens.